Sam Wu is not afraid of the dark - Tsang, Katie, 1987-; Tsang, Kevin (Tsang, Katie, 1987- Sam Wu is not afraid., 2019)
"I'm Sam Wu and there is not even the slightest possibility that I might be afraid of the dark. At all. EVER. But when I went camping in the woods with my best friend Bernard (at nighttime and everything!) I figured it would only be sensible to: 1) Light a campfire to deter Great Big Grizzly Bears/Attacking Aliens/Zombie Werewolves 2) Stay awake ALL night to make sure it works. Nooooo problem. Really!"--Page [4] of cover.